From Neutral Sentiment to Digital Governance: Instagram Reflections on the 2024 Indonesian Election - Yutanti, Widiya; Rahadi; Mohideen, Rosilawati Sultan; Selcuk, Mustafa (Journal of Local Government Issues, 2025)
This study aims to describe how sentiment on tempo.co Instagram after the announcement of the winner of the presidential election by the General Election Committee (KPU). Presidential and Vice-Presidential elections are one of the important moments in the political life of a country. Data was collected from Instagram posts on tempo.co from March to April 2024. This research uses a sentiment classification method using Support Vector Machines (SVM) and classifies into three categories, namely: positive, neutral and negative. The analysis was conducted by describing the phrases that appeared specifically related to the couple. The results showed that comments on the @tempodotco Instagram account related to the news about Prabowo-Gibran, Ganjar Pranowo-Mahfud MD, Anies Baswedan-Muhaimin Iskandar, neutral sentiments tend to be higher than positive and negative sentiments.  This suggests that the dominance of neutral sentiments in social media comments reflects the complex dynamics of digital interaction, where audiences collectively choose a moderate tone to avoid conflict. Comments that are positive or negative often come from a particular camp of supporters, while neutral comments reflect the voices of audiences trying to take a moderate position. Neutral audiences are often the silent majority who do not engage in violent discussions but still play a role in shaping opinions collectively.